Avaliação do teste de geração precoce no desenvolvimento de genótipos de soja com características agronômicas específicas - de Oliveira , Aluízio B; Sediyama, Tuneo; Sediyama, Carlos S; S Reis , Múcio; Silva , José Carlos (Revista Ceres, 2025)
Aiming to study the possibility of using with success the Early Generation Test to develop a new soybean variety, lines of the crosses ‘Paraná’ x ‘UFV-1’ and ‘IAC-2’ x ‘UFV-1’ in the F5 generation in 1981/82 and the Fg generation in 1982/83 were studied at Vigosa and Capindpolis in the State of Minas Gerais, Brazil.